PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL GURU SEJARAH TERHADAP PRESTASI BELAJAR MATA PELAJARAN SEJARAH PADA SISWA SEKOLAH MENENGAH ATAS NEGERI DI KOTA BANJARMASIN - Mursidah Mursidah (Universitas Lambung Mangkurat, 2016)
This study used quantitative approach with its design of correlational descriptive study. The research were taken place at all SMANs in Banjarmasin. The schools with 13 2387 eleventh grade students as the population while the samples were 5 schools and 96 eleventh grade students. Based on the finding of the study, it was yielded that (1)Partially, the pedagogical competency variable influenced the learning outcome of the students with counted t 1,982 higher than table t as 1,654 where the significant level is α =0,05. (2) partially, the professional competency variable influenced the learning outcome of the students with counted t as 2,685 higher that table t as 1,654 where the significant level is α = 0,05. The test result showed that the pedagogical competency of history teacher was very dominant in the learning outcome of the students at SMANs in Banjarmasin with unstandardized coefficient 0,290 higher than the professional competency 0,152. (3) The test result of both variables, pedagogical and professional competencies influenced the learning outcome of the students with counted F as 6,657, while the table F is 2,78. Based on the study, the researcher recommends : (1) there is significant influence between the pedagogical competency and professional competency toward the learning outcome of history subject at SMANs in Banjarmasin, therefore, related institutions need to evaluate and increase teacher competency. (2) teachers are recommended to work professionally develoving and increasing their competency to support the learning outcome of the students (3) other researchers can conduct the same research with different objects and competencies.Kata Kuci : Pengaruh, Persepsi Siswa, Pedagogik, Profesional, Prestasi Belajar, Sejarah